Non-natural Aldol Reactions Enable the Design and Construction of Novel One-Carbon Assimilation Pathways in vitro - Mao, Yufeng; Yuan, Qianqian; Yang, Xue; Liu, Pi; Cheng, Ying; Luo, Jiahao; Liu, Huanhuan; Yao, Yonghong; Sun, Hongbing; Cai, Tao; Ma, Hongwu (Frontiers in Microbiology, 2021)
Methylotrophs utilizes cheap, renewable one-carbon compounds, offering a promising green, sustainable and economical alternative to current sugar-based biomanufacturing. However, natural one-carbon assimilation pathways come with many disadvantages, such as complicated reaction steps, the need for additional energy and/or reducing power, or loss of CO2, resulting in unsatisfactory biomanufacturing performance. Here, we predicted eight simple, novel and carbon-conserving formaldehyde assimilation pathways based on the extended metabolic network with non-natural aldol reactions using the comb-FBA algorithm. Three of these pathways were found to be independent of energy/reducing equivalents, and thus chosen for further experimental verification. Then, two novel aldol reactions, condensing erythrose 4-phosphate and glycolaldehyde into 2R,3R-stereo allose 6-phosphate by DeoC or 2S,3R-stereo altrose 6-phosphate by TalBF178Y/Fsa, were identified for the first time. Finally, a novel formaldehyde assimilation pathway proceeding via allose 6-phosphate, named as the glycolaldehyde-allose 6-phosphate assimilation (GAPA) pathway, was constructed in vitro with a high carbon yield of 94%. This work provides an elegant paradigm for systematic design of one-carbon assimilation pathways based on artificial aldolase reactions, which could also be feasibly adapted for the mining of other metabolic pathways.